Actualistic Zooarchaeology in Central Western Argentina in Cave and Open Air Contexts - Clara Otaola (Ethnobiology Letters, 2014)
Many cultural and natural processes form the archaeological record. Taphonomy, the study of the transition of organic matter from living contexts (the biosphere) to geological contexts (the lithosphere), aids in understanding how agents and processes affect skeletal remains in the archaeological record. In this paper the results of an actualistic taphonomic study on deposition of bones in open-air and cave contexts in the high elevation Andes Mountains are presented. Results indicate that within the first three months after deposition many bones are displaced or removed from sites and that the agents that act in each context are different. Horizontal displacement of bones from their deposited locations is limited in the cave context but is dominant in the open air site. Carnivores appear to be responsible for moving bones in open-air contexts, and rodents appear to displace bones vertically in the cave context. Such naturalistic experiments are important in particular areas of the world in which local taphonomic processes vary.